Tricin, a Flavonoid Monomer in Monocot Lignification. Issue 4 (9th February 2015) - Lan, Wu; Lu, Fachuang; Regner, Matthew; Zhu, Yimin; Rencoret, Jorge; Ralph, Sally A.; Zakai, Uzma I.; Morreel, Kris; Boerjan, Wout; Ralph, John
Abstract : Tricin, a flavonoid, is a lignification monomer in grasses where it functions as a nucleation site for lignin polymer formation. Abstract: Tricin was recently discovered in lignin preparations from wheat ( Triticum aestivum ) straw and subsequently in all monocot samples examined. To provide proof that tricin is involved in lignification and establish the mechanism by which it incorporates into the lignin polymer, the 4′- O -β-coupling products of tricin with the monolignols ( p- coumaryl, coniferyl, and sinapyl alcohols) were synthesized along with the trimer that would result from its 4′- O -β-coupling with sinapyl alcohol and then coniferyl alcohol. Tricin was also found to cross couple with monolignols to form tricin-(4′- O -β)-linked dimers in biomimetic oxidations using peroxidase/hydrogen peroxide or silver (I) oxide. Nuclear magnetic resonance characterization of gel permeation chromatography-fractionated acetylated maize ( Zea mays ) lignin revealed that the tricin moieties are found in even the highest molecular weight fractions, ether linked to lignin units, demonstrating that tricin is indeed incorporated into the lignin polymer. These findings suggest that tricin is fully compatible with lignification reactions, is an authentic lignin monomer, and, because it can only start a lignin chain, functions as a nucleation site for lignification in monocots. This initiation role helps resolve a long-standing dilemma that monocot lignin chains do not appear to be initiated by monolignol homodehydrodimerization as they are in dicots that have similar syringyl-guaiacyl compositions. The term flavonolignin is recommended for the racemic oligomers and polymers of monolignols that start from tricin (or incorporate other flavonoids) in the cell wall, in analogy with the existing term flavonolignan that is used for the low-molecular mass compounds composed of flavonoid and lignan moieties.